Dynamic keys generation for internet of things - Omar Sapti Guma'a; Qasim Mohammed Hussein; Ziyad Tariq Mustafa Al-Ta'i (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In several aspects, interest in IoT has become considerable by researchers and academics in recent years. Data security becomes one of the important challenges facing development of IoT environment. Many algorithms were proposed to secure the IoT applications. The traditional public key cryptographic are inappropriate because it requires high computational. Therefore, lattice-based public-key cryptosystem (LB-PKC) is a favorable technique for IoT security. NTRU is one of a LB-PKC that based on truncated polynomial ring, it has good features, which make it to be an effective alternative to the RSA and ECC algorithms. But, there is LLL algorithm can success to attack it under certain conditions. This paper proposes modifications to NTRU public key cryptosystem to be secure against the lattice-based attack by using LLL algorithm, as well as a method for generating a new keys sequence dynamically. The results from simulations show that the performance of these modifications gives more secure from NTRU.